2012
DOI: 10.1021/nl3004896
|View full text |Cite
|
Sign up to set email alerts
|

The Race to the Pole: How High-Aspect Ratio Shape and Heterogeneous Environments Limit Phagocytosis of Filamentous Escherichia coli Bacteria by Macrophages

Abstract: While bioengineers ask how the shape of diagnostic and therapeutic particles impacts their pharmacological efficiency, biodistribution, and toxicity, microbiologists suggested that morphological adaptations enable pathogens to perhaps evade the immune response. Here, a shape-dependent process is described that limits phagocytosis of filamentous Escherichia coli bacteria by macrophages: successful uptake requires access to one of the terminal bacterial filament poles. By exploiting micropatterned surfaces, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 47 publications
5
107
1
1
Order By: Relevance
“…[38][39] Successful phagocytosis of filamentous E. coli bacteria by macrophages only happened when one of the terminal bacterial filament poles was accessible to macrophages. 40 Therefore, the contact between cellular membrane and end-caps of rods may be the key to effective cellular uptake via phagocytosis. However, the uptake of nanometer-sized rods by non-phagocytic cells was found to be affected by particle size and aspect ratio.…”
Section: Length Effect Of Rods On Cellular Uptake By Breast Cancer Cementioning
confidence: 99%
“…[38][39] Successful phagocytosis of filamentous E. coli bacteria by macrophages only happened when one of the terminal bacterial filament poles was accessible to macrophages. 40 Therefore, the contact between cellular membrane and end-caps of rods may be the key to effective cellular uptake via phagocytosis. However, the uptake of nanometer-sized rods by non-phagocytic cells was found to be affected by particle size and aspect ratio.…”
Section: Length Effect Of Rods On Cellular Uptake By Breast Cancer Cementioning
confidence: 99%
“…This entry is assumed to be caused by tip recognition following rotation initiated by the asymmetric elastic strain at the tube-bilayer interface. To determine whether such shape-and orientation-dependent mechanisms are also manifested by the phagocytosis of bacterial filaments, Mö ller et al [7] experimentally investigated the effects of shape and micro-environments on the phagocytosis of filamentous Escherichia coli bacteria by macrophages. They found that complete uptake occurs only if one of the terminal bacteria filament poles enters the cell first.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Rod-like or ellipsoidal particles, for example, mostly enter cells from their tip. 11,12 Oblate particles were found to be internalized more efficiently than spherical or ellipsoidal ones. 13 Surface chemistry of particles has also been shown to impact phagocytosis.…”
mentioning
confidence: 95%